2017
DOI: 10.1016/j.gore.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Paget's disease of the vulva: A review of 89 cases

Abstract: The purpose of this study was to retrospectively review the clinical characteristics and outcomes of a series of women with Paget's disease of the vulva. A retrospective review was performed of 89 women with Paget's disease of the vulva evaluated at a single institution between 1966 and 2010. Medical records were reviewed for demographic information, clinical data, pathologic findings, treatment modalities and outcomes. We found that the primary treatment was surgery for 74 (83.1%) patients, with positive marg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 14 publications
1
37
0
Order By: Relevance
“…1 The treatment for PDV is challenging due to frequent relapses, regardless of the treatment option. 12 Surgery has been the standard treatment for PDV but, because of its multifocal and subclinical skin involvement, surgical margins are frequently positive. As such, and although the results have not been encouraging (since involved surgical resection margins are neither associated with recurrence rates nor with overall survival), surgery with intraoperative margin control (Mohs microsurgery) is the preferred surgical method.…”
Section: Discussionmentioning
confidence: 99%
“…1 The treatment for PDV is challenging due to frequent relapses, regardless of the treatment option. 12 Surgery has been the standard treatment for PDV but, because of its multifocal and subclinical skin involvement, surgical margins are frequently positive. As such, and although the results have not been encouraging (since involved surgical resection margins are neither associated with recurrence rates nor with overall survival), surgery with intraoperative margin control (Mohs microsurgery) is the preferred surgical method.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis is made by skin biopsy and or immunohistochemistry staining of GCDFP-15, CK-7, CK-20 and CEA. Pathologically, EMPD of the vulva resembles mammary Paget’s of the nipple and areola 7 8…”
Section: Descriptionmentioning
confidence: 99%
“…Patients with EMPD of the vulva are at increased risk of synchronous or metachronous neoplasms including cervical, colorectal, and transitional epithelium carcinomas 7 8 10. Therefore, routine screening in some cases and prolonged surveillance has been recommended, although there are no clear guidelines.…”
Section: Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Studies by himself have since given a different emphasis, and a study published by the MD Anderson Cancer Center in 2017 showed that, of 89 patients who were followed up over 44 years, 46% had a synchronous or metachronous underlying carcinoma supporting the current recommended management of colonoscopy and cystoscopy on diagnosis, and stringent follow-up. [2] This represents an about-face on a condition fairly recently considered less significant than the more well-known Paget's disease of the breast. …”
mentioning
confidence: 99%